The Efficacy and Safety of Cilostazol in Ischemic Stroke Patients with Peripheral Arterial Disease (SPAD): Protocol of a Randomized, Double-Blind, Placebo-Controlled Multicenter Trial. Issue 1 (January 2015) - Jeng, Jiann-Shing; Sun, Yu; Lee, Jiunn-Tay; Lin, Ruey-Tay; Chen, Chih-Hung; Po, Helen L.; Lin, Huey-Juan; Liu, Chung-Hsiang; Sun, Ming-Hui; Sun, Mu-Chien; Chern, Chang-Ming; Lien, Li-Ming; et al.
Rationale: It is not uncommon for patients with ischemic stroke to have peripheral arterial disease (PAD). Patients with polyvascular diseases carry greater burden of atherosclerosis and higher risks of developing vascular events and death. More effective regimens, such as dual antiplatelet agents, may be more effective for controlling progression of atherosclerosis in secondary prevention. Aim: This study aims to evaluate whether cilostazol plus aspirin is more efficacious than aspirin alone for preventing progression of atherosclerosis in patients with ischemic stroke or transient ischemic attack (TIA) who also have peripheral arterial disease. Design: The Safety and Efficacy of Cilostazol in Ischemic Stroke Patients with Peripheral Arterial Disease (SPAD) study is a randomized double-blinded placebo-controlled trial. Patients with previous ischemic stroke or TIA who had been taking aspirin (100 mg per day), aged 50 years or older, with PAD in the lower limbs based on ankle-brachial index (ABI) <1·0 will be randomized into the treatment group with cilostazol (200 mg/day) or the placebo group on 1:1 basis. Study outcomes: Patients will be evaluated at 1, 3, 6, 9 and 12 months after randomization. The primary endpoint is difference in change in ABI between groups. The secondary and tertiary endpoints are the difference between groups in change in carotid intima-media thickness (IMT) and incidence rate of major cardiovascular events, including recurrent stroke, myocardial infarction, unstable angina, other vascular events, and death; and the safety measures, including major bleeding events, hemorrhagic stroke and death of any cause. Conclusion: The SPAD trial is the first study to evaluate the safety and efficacy of dual antiplatelet agents, aspirin plus cilostazol, in comparison with aspirin alone in patients with both ischemic stroke or TIA and PAD. Results from this trial will provide important information on the merit of adding cilostazol to aspirin for slowing down progression of atherosclerosis in patients with ischemic stroke and PAD.